Barriers and levers driving change in a STEM science subject in the Australian higher education sector: a focused study. Issue 1 (2nd January 2023) - Loughlin, Wendy A.; Whiteford, Chrystal M.; Geelan, David R.; Brown, Raymond A. J.
ABSTRACT: Background: This study explored the challenges around enacting change in a STEM (Science, Technology, Engineering and Mathematics) subject at an Australian higher education institution and examined key elements required to ensure change. Purpose: The purpose of the study was to examine the barriers and levers driving change during the collaboration of discipline experts, in both science and education disciplines and professional staff across education and science faculties to change the delivery of an existing subject within a science faculty, from traditional lectures to an active learning approach. Sample: Participants from the education faculty and science faculty formed the participant interview pool of five academics for this study. Design and Methods: Research design of semi-structured interviews of participants was conducted to answer the research questions. Instruments were used to test the research questions, such as factors to facilitate and support change to teaching a science subject and the elements required for successful interdisciplinary collaboration for bringing about change to the teaching of a science subject. Thematic analyses were conducted on the data responses to answer the research questions. Results: The findings revealed that participants found that factors such as time, resources, understanding of and commitment to the proposed change represented potential barriers to change in the subject. The existence of multiple, time-sensitive champions, additional human resources and a collaborative network of participants, however, were identified as some of the key elements that supported enacting changes to a science subject. Conclusions: The findings of the study provide insights into interdisciplinary collaborations enacting changes to the teaching of a science subject. For instance, the need for establishment of a dynamic network of participants engendered with multiple interdisciplinary expertise, as well as the need for a change champion and implementation champion, throughout the curriculum re-design, planning and implementation phases of the change.